Osseous and Cartilaginous Nasal Reconstruction - Hahn, Samuel (Facial Plastic Surgery, 2017)
The nose is a complex, three-dimensional structure that is supported by a framework of osseous and cartilaginous structures. Disruption of this framework can result in nasal deformity and functional deficits. Nasal reconstruction requires restoration of the osseous and cartilaginous framework. This requires careful preoperative assessment of the nasal defect and understanding the nasal and facial aesthetics that are supported by the osseous and cartilaginous support structures. Structural grafts can be classified as restorative, supportive, or contouring. Surgeons must understand the requirements for each type of grafting and which materials to use to provide the necessary structural reconstruction. Autogenous, homologous, and allogenic materials can be used for reconstruction of the structural deficits. Autogenous grafts from the septum, ear, rib, and calvarium are preferred for structural reconstruction, but surgeons should be well versed with alternative structural grafting materials. Smaller defects can be corrected through cartilaginous grafts, while larger defects require more rigid bony support to withstand the contractive forces of wound healing. Titanium mesh can serve as a viable alternative for rigid structural reconstruction. The ultimate goal of nasal reconstruction is to restore nasal form and function, and successful reconstruction starts with establishing a stable, functional, and anatomically sound osseocartilaginous framework.
Keywords: nasal reconstruction; structural grafts; osseocartilaginous; bone graft; cartilage graft